1970
DOI: 10.1111/j.1365-2389.1970.tb01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpine Podzol Soils on the Ben Lawers Massif Perthshire

Abstract: WITH 2 PLATES SummaryCharacteristics of the soils include well-defined horizons, very low pH values and base saturation percentages, and a slight but general increase in the silt-plusclay content down the profile. X-ray diffraction shows that the soil clays are rich in mica and chlorite with subsidiary amounts of kaolinite, goethite, and lepidocrocite. The general distribution of the clay minerals in the profiles studied suggests that the weathering of chlorite leads to the formation of kaolinite in the A hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Geikie, 1894;Sissons, 1967). A number of authors contested this opinion, basing their arguments on the survival of tors on high ground (Linton, 1949(Linton, , 1955, the thickness of mountain-top detritus (Ragg and Bibby, 1966), the presence of halloysite and kaolinite in mountain soils (Stevens and Wilson, 1970) and the distribution of blockfields (Godard, 1965), but these arguments are now acknowledged to be equivocal (e.g. Sugden, 1968;Sissons, 1976;Ballantyne et a/., 1987;Hall and Mellor, 1988;Ballantyne and Harris, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Geikie, 1894;Sissons, 1967). A number of authors contested this opinion, basing their arguments on the survival of tors on high ground (Linton, 1949(Linton, , 1955, the thickness of mountain-top detritus (Ragg and Bibby, 1966), the presence of halloysite and kaolinite in mountain soils (Stevens and Wilson, 1970) and the distribution of blockfields (Godard, 1965), but these arguments are now acknowledged to be equivocal (e.g. Sugden, 1968;Sissons, 1976;Ballantyne et a/., 1987;Hall and Mellor, 1988;Ballantyne and Harris, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell (1955), on the basis of decrease in amount of chlorite with depth and an even distribution throughout the particle-size range of the clay fraction, has considered chlorite to be highly stable in many Scottish soils, and Ball (1966) could find no clear pedogenic trend and no indication of new mineral phases being formed from chlorite in highly chloritic brown earths and rankers of Snowdonia. On the other hand, Perrin (1971) reported that chlorite derived from Lower Palaeozoic shales is destroyed fairly rapidly in the soil, and others have reported that the mineral readily weathers to oxides of iron and aluminium (MacEwan, 1948), saponite or vermicu lite (Smith, 1962), kaolinite (Stevens and Wilson, 1970) and vermiculite or amorphous silica (Adams et al ,197 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given time and stability, it is likely that they would develop into alpine podzols (Romans et al 1966;Stevens & Wilson 1970), podzols or brown soils (Ellis 1980a), depending on the lithology and climatic conditions. As such, they can be classed as inceptisols (Ragg 1973).…”
Section: Classification Of Regolithsmentioning
confidence: 99%
“…Even if clays were being formed, the coarse texture and free-draining nature of the regoliths mean that they would be rapidly removed by leaching (Reid et al 1981;Smith et al 1983). Throughflow is known to be) important in arctic-alpine regoliths (Stevens & Wilson 1970;Ragg 1973;Harris & Ellis 1980;Lewis & Grant 1980), and could result in the removal of any clay-sized material. This removal of fines by throughflow is a well-known phenomenon, and has been termed 'impoverishment' by Duchafour (1982).…”
Section: Origin and Development Of Regolithsmentioning
confidence: 99%